2020
DOI: 10.18203/issn.2455-4510.intjresorthop20203710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, gender and body mass index on the efficacy of tranexamic acid in total knee arthroplasty

Abstract: <p class="abstract"><strong>Background:</strong> Tranexamic acid (TXA) is effective and safe in decreasing blood loss and transfusion rate in total knee arthroplasty (TKA). Few studies focused on the role of patients’ characteristics on the efficacy of TXA in TKA. The purpose of this study was to conduct a retrospective analysis to investigate if age, gender and BMI influence the efficacy of TXA in reducing perioperative blood loss in TKA.</p><p class="abstract"><strong>Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Few studies have reported a correlation between sex and TXA use during a HTO. However, a similar correlation has been reported in spinal surgery, 30 , 31 arthroplasty replacement, 32 , 33 , 34 and orthognathic surgery. 35 Hypotheses for the possible mechanisms are as follows.…”
Section: Discussionsupporting
confidence: 81%
“…Few studies have reported a correlation between sex and TXA use during a HTO. However, a similar correlation has been reported in spinal surgery, 30 , 31 arthroplasty replacement, 32 , 33 , 34 and orthognathic surgery. 35 Hypotheses for the possible mechanisms are as follows.…”
Section: Discussionsupporting
confidence: 81%
“…Both Viegas et al and Meng et al in studies from 2020 and 2018, respectively, demonstrated that using TXA in patients with higher BMI would result in smaller blood losses when compared with TXA usage in patients with smaller BMIs. 18,30 Higher BMI is associated with higher values of plasminogen activator inhibitor-1 (PAI-1), [30][31][32][33] a protein synthesized by the endothelium, liver, and adipocytes. 31,33,34 PAI-1 prevents the conversion of plasminogen to plasmin and subsequently produces antifibrinolytic effects.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Patient-specific instrumentation (PSI) emerged in the last two decades as an alternative to CI, aiming to improve accuracy and cost effectiveness in daily use, as well as reduce operating times, and blood loss caused by TKA. 1,3,5,8,12,13 TKA frequently presents perioperative blood losses, due to soft-tissue dissection and bone cuts, [14][15][16][17][18] estimated between 1,500 and 2,000 mL, with a predictable decrease of 3 g/dL of hemoglobin (Hb) for every 1,000 mL of blood loss. 12,19 Blood loss increases morbidity, mortality and dissatisfaction of patients but it also prolongs hospital admission and increases costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested female might benefit more than male on blood management from TXA. Some studies in arthroplasty replacement [ 3 5 ] and orthognathic surgeries [ 6 ] presented similar actions. Although the mechanism was still elusive, some hypotheses were given.…”
mentioning
confidence: 94%